The Pavlov Department of Physiology: A Scientific History - Klimenko, Victor M.; Golikov, Juri P. (The Spanish Journal of Psychology, 2003)
The scientific adventure of the Ivan Pavlov Department of Physiology is traced from Pavlov’s and his students pioneer work on “psychic salivation” to the times of the Biological Station at Koltushi. The development of the Department after Pavlov’s death is described and the research trends of the three present laboratories (Neurobiology of Integrative Brain Functions, Psychophysiology of Emotions, and Neurodynamic Correction of Psycho Neurological Pathology) are discussed.